Modifikasi Pengolahan Minyak Kelapa Untuk Meningkatkan Kualitas Ampas Minyak Kelapa. Kajian Dari Konsentrasi Na-metabisulfit dan pemarutan. - Sukamto, Sukamto; Harmanto, Harmanto (Jurnal Teknologi Pertanian, 2004)
The waste of coconut oil by dry processing have not be used, because that was not higienes. The objective of this research is to study  effect of  Na-metabisulfit  concentration and sliecing waste quality.  The method used in the research  was Randimized Completed Block Design consisting   Na-metabisulfit  concentration rate (0, 750 and 1500 ppm) and sliecing (be slieced and was not slieced).  The quality parameters evaluated in waste of cocnut  were water conten,  protein, free fatid acid, silfit residue, and organoleptic aspects including  smell  and colour.     The statisical analiysis result indicated that sliecing  were significant on water content, free fatid acid, and smell.  Na-metabisulfit  concentrations  were  significant on the protein, colour and smell. Key word : oil, coconut, Na-metabisulfit